Spectrum of diseases in a medical ward of a teaching hospital in a developing country - Pokharel, BR; Humagain, S; Pant, P; Gurung, R; Koju, R; Bedi, TRS (Journal of College of Medical Sciences-Nepal, 2012)
Communicable and respiratory tract diseases especially chronic obstructive pulmonary diseases are the main reasons of admission in medical ward of low and middle income countries. This is different from the developed countries where non communicable diseases are the main reasons of hospital admission. In developing countries the data of hospital admission are still lacking. Therefore this study will help us to assess the common patterns of diseases admitted in a medical ward, the average length of hospital stay etc. The record of 1040 hospitalized patients in medical ward was analyzed for the period of six months from Jan 2010 to Jun 2010. Patient’s medical records were retrieved and data analysis was done to obtain age, sex, common diagnosis, the affected system and the duration of the hospital stay. The data was analyzed by using SPSSV 16. After reviewing the data the most common age of patients being admitted were between 46-65 years (31.5%) followed by more than 65 years (25%) between 26-45 years (21.28%) and less than 25 years (21.28%). Among the admitted patients females were more than the males except in neurolog ward. The most effected system was respiratory (31.73 %),and the most common diagnosis was Chronic obstructive pulmonary diseases (23.17%). The next common system involved was gastroenterology including liver (18.64%) ,genitourinary (12.01%), cardiovascular ( 11.34%), neurology (9.23%), endocrine (4.80%) hematology (2.30%). The cause for hospital admission by infection in different system was (30.08%) The average duration of hospital stay of the patients was less than 7 days. The respiratory diseases and the infectious disease are the most common disease in Nepal. The communicable diseases still hold a greater position, while non communicable diseases are main reasons for admission to the medical wards in developed countries. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 7-11 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6831